DIABETES AND ORAL HEALTH - Akramova Zarnigor Ravshanovna; Usmanov Firdavs Bakhtiyarovich (Web of Journals Publishing, 2025)
This article discusses the impact of diabetes on oral health, the main dental complications, and measures for their early detection and prevention. It also discusses the importance of cooperation between dentists and endocrinologists.
Keywords: Diabetes, oral health, periodontitis, dry mouth, candidiasis, dental complications, salivation, gingivitis, dental hygiene, immune system.